2015
DOI: 10.1186/s40529-015-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual specialization in phenology in dioecious Ficus benguetensis and its consequences for the mutualism

Abstract: BackgroundTiming of reproductive events has become central in ecological studies linking success in pollination and seed dispersion to optimizing the probability and periods of encounters with pollinators or dispersers. Obligate plant–insect interactions, especially Ficus–fig wasp mutualisms, offer striking examples of fine-tuned encounter optimization as biological cycles between mutualistic partners are deeply dependent on each other and intertwined over generations. Despite fig flowering phenology being cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Extensive long-distance dispersal of pollinating wasps, aided by passive air column travel [73,74], has been documented repeatedly in monoecious figs and is ranked among the furthest known in plants [75][76][77]. For example, Ahmed et al [77] showed successful pollination across distances over 160 km in monoecious F. sycomorus L. Meanwhile, synchronous intra-tree flowering, between tree asynchrony [78], and low densities of monoecious figs mean host-specific pollinators must travel long distances. Most populations showed negative or small positive F IS values (Table A1), which is consistent with regular outcrossing associated with high dispersal events.…”
Section: Genetic Diversity Population Dynamics and Phylogeographic Pa...mentioning
confidence: 99%
“…Extensive long-distance dispersal of pollinating wasps, aided by passive air column travel [73,74], has been documented repeatedly in monoecious figs and is ranked among the furthest known in plants [75][76][77]. For example, Ahmed et al [77] showed successful pollination across distances over 160 km in monoecious F. sycomorus L. Meanwhile, synchronous intra-tree flowering, between tree asynchrony [78], and low densities of monoecious figs mean host-specific pollinators must travel long distances. Most populations showed negative or small positive F IS values (Table A1), which is consistent with regular outcrossing associated with high dispersal events.…”
Section: Genetic Diversity Population Dynamics and Phylogeographic Pa...mentioning
confidence: 99%
“…An efficient and widespread strategy is used by Ficus species to maintain the population of their mutualistic pollinator as well as feeding seed dispersers. Nevertheless, studies like this one have shown the phenological differences between male and female trees, that is, female individuals produce less figs and have fewer production peaks ([ 23 , 24 , 30 , 31 ], this study). Thus, female trees have not been selected to produce frequent and asynchronous crops like male trees, which are required to maintain the population of fig wasps [ 10 , 24 ].…”
Section: Discussionmentioning
confidence: 60%
“…Leaf unfolding and reproduction occur that also serve as the plants’ carbon sink, and the manifestations of the phenological cycles of these two processes correlate with each other 27 , 45 . These correlations could be the reason for both genders that tender leaf abundances negatively correlated with Phase C fig abundances, and that Phase C fig abundances positively correlated with mature leaf abundances.…”
Section: Discussionmentioning
confidence: 99%